2011
DOI: 10.12934/jkpmhn.2011.20.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Child-Rearing of Filipino Married Immigrant Women

Abstract: Purpose:The purpose of this study was to identify experiences of immigrant women from Philippines in childrearing. Methods: The study design was a qualitative research. Participants were 15 Filipino immigrant women living in rural Korea. Average age was 37 and average duration of marriage was 11 years. Data were collected through in-depth interviews and participants were interviewed once or twice between December 2009 and February 2010. Data were analyzed with Colaizzi's (1978) phenomenological methodology. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
2
4
0
1
Order By: Relevance
“…Multicultural children presented significantly lower scores for the mother-child relationship and school adjustment than non-multicultural students, in addition to their poorer scores for health behaviors, suggesting that multicultural children's environmental support system may also be vulnerable. This study supports the results of previous studies [15,25] that reported poor-quality mother-child relationships in multicultural families, due to the fact that mothers of multicultural families immigrate at the time of marriage and, in a short time frame, experience the drastic change of childbirth in addition to facing the burden of child-rearing, a combination that contributes to high parenting stress and low maternal identity, placing them at a greater risk of difficulties in mother-child bonding from the early stages of their children's lives [25]. Subsequently, it becomes easier to use physical instead of verbal punishment as the child grows and the mother's Koreanlanguage proficiency falls short compared to that of her child, and school enrollment may cause mother-child conflicts due to the child's disrespect toward the mother, who is unfamiliar with educational programs and culture in Korea [15].…”
Section: Chnrsupporting
confidence: 94%
See 2 more Smart Citations
“…Multicultural children presented significantly lower scores for the mother-child relationship and school adjustment than non-multicultural students, in addition to their poorer scores for health behaviors, suggesting that multicultural children's environmental support system may also be vulnerable. This study supports the results of previous studies [15,25] that reported poor-quality mother-child relationships in multicultural families, due to the fact that mothers of multicultural families immigrate at the time of marriage and, in a short time frame, experience the drastic change of childbirth in addition to facing the burden of child-rearing, a combination that contributes to high parenting stress and low maternal identity, placing them at a greater risk of difficulties in mother-child bonding from the early stages of their children's lives [25]. Subsequently, it becomes easier to use physical instead of verbal punishment as the child grows and the mother's Koreanlanguage proficiency falls short compared to that of her child, and school enrollment may cause mother-child conflicts due to the child's disrespect toward the mother, who is unfamiliar with educational programs and culture in Korea [15].…”
Section: Chnrsupporting
confidence: 94%
“…Especially when their children become elementary school students and begin to follow the regular school curriculum, foreign mothers face difficulties in guiding their children to learn due to their different sociocultural background, the unfamiliarity of the curriculum, and their poor Korean proficiency. The low parenting efficacy that stems from mothers' poor ability to guide their children's learning further disturbs their relationship with their children, and it therefore may be easier for children to disregard their mothers or demonstrate negative attitudes toward them [15]. This interrupts the formation of the mother-child relationship and interfere with mothers' roles as the health behavior educators and facilitators for their children.…”
Section: Need For Studymentioning
confidence: 99%
See 1 more Smart Citation
“…선행연구에서 자녀가 결혼이주여성의 정신건강에 보호효과가 있는 것으로 보고되었으며 (Song & An, 2011), 가족 구성원 간의 애착 관계, 지지여부의 보호효 과 (Masten, 2007;Park & Yoo, 1999)도 확인되었다.…”
Section: 가족 관련 보호요인으로 '자녀 여부'와 '가정생활만족도'unclassified
“…Different cultural backgrounds and differences in consciousness have caused conflicts and difficulties among multicultural family members. In particular, immigrant women may have difficulties with communication due to poor language competence, which can lead to difficulties with childcare [3]. The foreign immigrant wives in Korea do not want their children to experience the same discrimination and prejudice that they experience.…”
Section: Introductionmentioning
confidence: 99%